CASTA ESTEBAN, CAROLINA LAMAS DE LETONA, AND BLANCA DE GASSO: THREE WOMEN FROM THE SPANISH SECOND ROMANTICISM - Begoña A. REGUEIRO SALGADO (Studia Universitatis Babeş-Bolyai. Philologia, 2017)
Casta Esteban, Carolina Lamas de Letona, and Blanca de Gassó: Three Women from the Spanish Second Romanticism. This paper represents the first step towards recovering some women writers from the Spanish Second Romanticism: Casta Esteban, Carolina Lamas de Letona, and Blanca de Gassó, who come to join Rosalíade Castro. All these writers were read and highly appreciated by the male members of this Group.